Pendekatan Terbaru EME - Safei, Su'aidi (2011)
Prospects for Malaysia to be accepted in the eyes of the world are very prominent and visible. Education Malaysia Egypt (EME) has been acting within its strategic framework, to set up the Meeting Council Secretariat of State House Officers (SMMPRN). Among the objectives of its establishment, to generate synergies of cooperation and collaboration of all the state houses in Egypt and EME in executing programs/academic activities and partial academic.